Prevalence and health-care seeking pattern of patients with functional diarrhoea in an urban community of Bangladesh (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jan;19(1):85-88.The abstract of this article is available on the PubMed website